2013
DOI: 10.3762/bjoc.9.64
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of base-catalyzed reactions of cyclic 1,2-diones: cyclobutane-1,2-dione

Abstract: SummaryThe reaction of cyclobutane-1,2-dione with hydroxide was studied by a variety of ab initio (MP2, SCS-MP2, CCSD(T), CEPA/1) and density functional (M06-2X) methods. Three possible reaction paths of the initially formed tetrahedral adduct leading to either 1-hydroxycyclopropane-1-carboxylate (benzilic acid type rearrangement, path A), α-oxobutanoate (path B) or γ-oxobutanoate (path C) were considered. Although the latter two products show similar or even more negative Gibbs free energies of reaction than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Our results only show the bond breaking of the pyrazole to the ethane backbone, but under all conditions used, we do not observe two pyrazole on one of the ethane carbon. 37 A point raised from this study is the difference in the ligands present in the structures of Cu 6 and Cu 16 which are prepared from Cu-nitrate and Cu-BF 4 , respectively, compared to that of Cu 8 obtained from Cuacetate. In the first two compounds, the central ligand is et with the coordinating Cu 6 cores looking identical, but for the latter, the inner ligands are the esters of et with the corresponding alkyl groups of the alcohol solvents.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results only show the bond breaking of the pyrazole to the ethane backbone, but under all conditions used, we do not observe two pyrazole on one of the ethane carbon. 37 A point raised from this study is the difference in the ligands present in the structures of Cu 6 and Cu 16 which are prepared from Cu-nitrate and Cu-BF 4 , respectively, compared to that of Cu 8 obtained from Cuacetate. In the first two compounds, the central ligand is et with the coordinating Cu 6 cores looking identical, but for the latter, the inner ligands are the esters of et with the corresponding alkyl groups of the alcohol solvents.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…However, we cannot crystallographically confirm the rearrangement, that is, the migration of the pyrazole from one ethane carbon to the other. Our results only show the bond breaking of the pyrazole to the ethane backbone, but under all conditions used, we do not observe two pyrazole on one of the ethane carbon . A point raised from this study is the difference in the ligands present in the structures of Cu 6 and Cu 16 which are prepared from Cu-nitrate and Cu-BF 4 , respectively, compared to that of Cu 8 obtained from Cu-acetate.…”
Section: Resultsmentioning
confidence: 99%
“…The base-catalyzed reaction of cyclobutane-1,2-dione was recently investigated by Sultana and Fabian with a variety of ab initio and density functional (M06-2Â) methods. 77 The authors examined three reaction pathways, whose products are 1-hydroxycyclopropane-1-carboxylate, a-oxobutanoate and g-oxobutanoate, respectively. Based on the activation and reaction energies computed with LPNO-CEPA, it was concluded that the formation of 1-hydroxycyclopropane-1-carboxylate via the benzilic acid rearrangement is the only feasible reaction pathway, in agreement with previous experimental observations.…”
Section: Organic Chemistrymentioning
confidence: 99%
“…Based on the activation and reaction energies computed with LPNO-CEPA, it was concluded that the formation of 1-hydroxycyclopropane-1-carboxylate via the benzilic acid rearrangement is the only feasible reaction pathway, in agreement with previous experimental observations. 77 Finally, in the validation of the DLPNO-CCSD(T) method, a benchmark dataset consisting of 51 reaction energies, for which accurate results have been recently published by Friedrich and Ha ¨nchen, 78 was considered. The database covers a large set of chemically interesting processes (e.g.…”
Section: Organic Chemistrymentioning
confidence: 99%